2018
DOI: 10.1002/humu.23661
|View full text |Cite
|
Sign up to set email alerts
|

Novel pathogenic variants in filamin C identified in pediatric restrictive cardiomyopathy

Abstract: Restrictive cardiomyopathy (RCM) is a rare and distinct form of cardiomyopathy characterized by normal ventricular chamber dimensions, normal myocardial wall thickness, and preserved systolic function. The abnormal myocardium, however, demonstrates impaired relaxation. To date, dominant variants causing RCM have been reported in a small number of sarcomeric or cytoskeletal genes, but the genetic causes in a majority of cases remain unexplained, especially in early childhood. Here, we describe two RCM families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…Same conclusions were drawn from the explanted hearts in the family with p.Y2563C mutation [ 57 ]. Conversely, the expression of filamin C variants in C2C12 cells led to aggregate formation [ 57 ]. Specifically, in cells expressing p.P2298L construct, aggregates were often observed in the proximity of nuclei [ 57 ].…”
Section: Filamin C and Cardiomyopathiesmentioning
confidence: 68%
See 3 more Smart Citations
“…Same conclusions were drawn from the explanted hearts in the family with p.Y2563C mutation [ 57 ]. Conversely, the expression of filamin C variants in C2C12 cells led to aggregate formation [ 57 ]. Specifically, in cells expressing p.P2298L construct, aggregates were often observed in the proximity of nuclei [ 57 ].…”
Section: Filamin C and Cardiomyopathiesmentioning
confidence: 68%
“…Two more FLNC mutations have been reported in RCM families with childhood onset—c.6893C>T (p.P2298L) and c.7688A>G (p.Y2563C) [ 57 ]. The study of explanted cardiac tissue in the family with p.P2298L variant showed no inclusions or depositions and the sarcomere structure presented regular and without disarrays [ 57 ]. Same conclusions were drawn from the explanted hearts in the family with p.Y2563C mutation [ 57 ].…”
Section: Filamin C and Cardiomyopathiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, the mutations are distributed in all domains of FLNC protein having mutational hotspots in R24 (p.Trp2710Ter) that is found in patients from diverse ethnic origins [13,137]. Biochemical analysis revealed that many of the mutations lead to aggregation of FLNC proteins [99,121,137] (Figure 4). For example, expression of four FLNC mutants (p.V123A, p.A1539T, p.R2133H, and p.A2430V) in cardiac tissue culture cells resulted in the formation of actin aggregates, although FLNC p.A1539T mutant protein itself appears to be soluble [121].…”
Section: Genotype-phenotype Correlations In Flnc Mutationmentioning
confidence: 87%